Exploring the Effectiveness of Virtual Reality in Promoting Cultural Heritage Preservation - Georgiou, Andreas; Kontou, Panagiota; Vasilakis, Georgios; Nikolaidou, Sophia; Kouroupaki, Eftychia (Journal of Computer Engineering, 2026)
The aim of our work is to investigate the applicability of Virtual Reality (VR) in raising awareness of users in relation to the destruction of important monuments. The proposed methodology involves the exposure of users to three virtual environments displaying the original state of a monument, the current state and the predicted future state of the same monument in the case that the monument is not maintained. The exposure to the three states of the same building allows the user to experience the “glorious days” of a monument and compare them to the current and future states in an attempt to realize the level of destruction that could occur to the building if the monument is not maintained properly. As part of a pilot case study, a number of volunteers were asked to navigate in virtual environments depicting the three chronological states of a landmark building. Preliminary results indicate a significant increase of the intensity of negative emotions of the users, indicating the applicability of VR in alerting the society toward the destruction of important monuments